Structure of the Useful Adaptive Result in the Systemic Organization of Physiological Functions as a Subject of Scientific Analysis: History and Prospects of Research - Lapkin, M. M.; Pertsov, S. S.; Zorin, R. A. (Bulletin of experimental biology and medicine, 2023)
The concept of “useful adaptive result”, a key concept in the theory of functional systems by P. K. Anokhin, is discussed. A large body of works devoted to this problem, in the historical aspect and on the basis of results of own researches, allows concluding that useful adaptive results of the system organization of physiological functions include not only the event arising as a result of activity of the system, but also the physiological cost of this activity. The ratio of the physiological cost and performance indicators gives an idea of the effectiveness of system activity and is its integral characteristic. The main approaches to estimation of physiological cost and efficiency of activity are discussed, as well as possibilities of using methods of applied mathematics (correlation and cluster analysis, artificial neural network technology) to describe system organization of physiological functions in healthy people. The question of the use of the proposed regulations to describe the system organization of physiological functions in patients with Parkinson’s disease and epilepsy is considered.